BILATERAL CLEFT PALATE REPAIR BY USING TONGUE FLAP FOLLOWED BY ALVEOLAR BONE GRAFTING - A CASE REPORT - Satti, Memuna Kausar; Qasim, Zainab; Rais, Farwa; Iqbal, Ayousha; Shoaib, Maahin; Ghaffar, Asad (Pakistan Armed Forces Medical Journal, 2021)
A clinical case of bilateral cleft palate repair using previous tongue flap followed by Alveolar Bone Grafting (ABG). After pre-surgical orthodontics a surgical procedure whereby previous tongue Flaps were reflected, nasal beds were prepared on both sides. A cortico-cancellous bone of 2 cm was harvested from iliac crest and grafted in clefts. Patient is kept on follow up to monitor healing, postoperative results and any post- operative complication.